Malar Reconstruction with Anterior Bilobed Cheek Flap. Issue 4 (April 2018) - Ueda, Koichi; Akamatsu, Jun; Sugita, Naoya; Nuri, Takashi; Otsuki, Yuki
Abstract : Summary: A 66-year-old man had developed a tumor on his right cheek. A biopsy revealed basal cell carcinoma. The ulcerative cancer and zygomatic bone were resected. We designed an anterior bilobed cheek flap to reconstruct the cheek skin defect. The postoperative clinical course was uneventful.